Slope stability and disaster mechanisms in the Honghe Hani Terraces: a systematic review - Valisoasarobidy José Gabriel; Ruihong Wang; Doshroth Mahato; Can Wei (Egyptian Journal of Remote Sensing and Space Sciences, 2025)
Slope stability and disaster mechanisms are critical concerns for the Honghe Hani Terraces (HHT), a UNESCO World Heritage Site renowned for its unique agricultural and cultural heritage. This systematic review examines the factors influencing slope instability, the role of climatic conditions, and the impact of agricultural practices in the region. Using the PRISMA framework, 105 studies from 2000 to 2023 were analyzed, identifying key trends and research gaps through bibliometric and thematic analyses. The findings reveal that natural factors, such as rainfall intensity and soil properties, interact with anthropogenic factors, including land use changes and traditional farming practices, to significantly influence slope stability. While traditional agricultural techniques like terracing can enhance soil conservation, improper management and recent land use changes, such as deforestation and urbanization, have intensified instability. Numerical simulations highlight the complex interplay between rainfall, irrigation, and slope dynamics, emphasizing the need for integrated management strategies. The review underscores the importance of combining traditional knowledge with modern technologies, such as remote sensing and GIS, to develop sustainable land management practices and early warning systems. Community involvement and capacity-building are also essential for effective mitigation. Despite limitations, such as methodological variability and data inconsistencies, this review provides a comprehensive understanding of slope stability in the HHT and proposes future research directions to enhance disaster resilience and preserve this unique cultural landscape.